Influence of the ratio of oxides and temperature on the structure formation of alkaline hydro-aluminosilicates - Kryvenko, Pavlo; Kyrychok, Volodymyr; Guzii, Sergii (Eastern-European Journal of Enterprise Technologies, 2016)
In the course of optimization of compositions of alkaline hydro-aluminosilicates of general structural formula – (0,7÷1Na2O+0÷0,3K2O)·Al2O3·(2÷7)SiO2·nH2O, it is established that the phase composition of artificial stone depends more on the ratio of basic oxides; the temperature of hardening in the range of 20÷80 °С increases the speed of structure formation of zeolite-like phases. A determining factor of influence on the type of hydrated new formations is the ratio of SiO2/Al2O3; its increase leads to the creation of zeolite-like phases with high content of silica in its composition. At hardening of alkaline hydro-aluminosilicate of the given structural forms under standard conditions of hardening, providing for a high degree of crystallinity of structure, optimal is the ratio SiO2/Al2O3=4÷5. Introduction of potassium ions into the composition of hydro-aluminosilicate contributes to obtaining potassium and sodium–potassium zeolite–like new formations and to increasing the degree of crystallinity of the indicated phases. To accelerate the structure formation of alkaline hydro-aluminosilicate under standard conditions of hardening, it is necessary to introduce potassium oxide at K2O/R2O=0,15÷0,3. With an increase in the temperature of hardening of alkaline hydro-aluminosilicate from 20 to 80 °, the phase composition of artificial stone remains practically unchanged; however, this leads to an increase in the velocity of structure formation and the degree of crystallinity of artificial stone. As a result of optimization, we determined optimum structural formula of hydro-aluminosilicate (0,8Na2O+0,2K2O)·Al2O3·4,5SiO2·nH2O, which makes it possible under standard conditions of hardening to obtain water-resistant artificial stone by the synthesis in the composition of hydrated new formations of zeolite-like minerals of the type of zeolite Na–A; sodium and potassium heulandite, as well as sodium potassium phillipsite.